Peran Aplikasi Sistem Informasi Aparatur Sipil Negara (SIASN) Layanan SKK dalam Mendukung Efisiensi Operasional Direktorat Status dan Kedudukan Kepegawaian di Badan Kepegawaian Negara (BKN) - Syafa Kamila Ardyaputri; Darmeinis Darmeinis (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to examine the role of the SIASN application in SKK services to support operational efficiency of the Directorate of Personnel Status and Position at the State Civil Service Agency. This research uses a qualitative method with a descriptive approach. The subjects of this research are employees at the Directorate of Personnel Status and Position who are directly involved in using the SKK Services SIASN application. Data was collected through in-depth interviews, observation and documentation. Data analysis was carried out by identifying patterns and themes that emerged from the data collected. The research results show that the use of the SKK Service SIASN application significantly increases operational efficiency in the Directorate of Personnel Status and Position. This application simplifies the administration process, reduces the time required to complete tasks, and increases data accuracy. Thus, the SKK Services SIASN application plays an important role in supporting more efficient and effective operations within the Directorate of Personnel Status and Position.